Housing Market Makes Spurious Prosperity in China’s Economy - Yu, Zihang (Université d'Ottawa | University of Ottawa, 2016)
Unaffordable Housing price problem in China’s metropolises could be attributable to excessive investment in real estate market. However, the real estate market’s establishment here is not determined by market itself but largely supervised by Government, this is what we say one of the representative cases of “big government and relatively small market”. Although real estate market in China is more developed than other markets in China, government’s constant intervention behaviour, which initially is in order to achieve goal of economic growth, indeed has deviated the real estate market from sustainable development path. It is specifically manifested in superfluous private investment and public investment flowing into real estate market. And the high investment level always corresponds to the high price level, which causes the “housing price unaffordability” in cites. Moreover, it gradually became the fact that real income growth of Chinese residents in fact cannot catch up with housing price growth, and even to the extent that high expense in housing makes Chinese residents “poor”. And at the same time capital over-accumulated in real estate industry makes other industries “weak” and then has adverse impact on national output in long-run.